A multicenter survey of effects and challenges of an 8K ultra‐high‐definition endoscopy system compared to existing endoscopy systems for endoscopic surgery. Issue 1 (18th August 2022) - Kono, Yohei; Inomata, Masafumi; Sumi, Yasuo; Ohigashi, Seiji; Ieiri, Satoshi; Shin, Toshitaka; Shinohara, Toshihiko; Abe, Tetsuya; Osoegawa, Atsushi; Fujisawa, Masato; Mori, Toshiyuki; Kitagawa, Yuko; et al.
Abstract: Introduction: 8K ultra‐high‐definition (UHD) images enabling clearer recognition of anatomical structures could contribute to further development of surgical techniques and advanced applications in endoscopic surgery fields. This study aimed to clarify effects and challenges of endoscopic surgery with 8K UHD endoscopy compared to existing endoscopy systems. Methods: In this multicenter, cross‐sectional, questionnaire survey, data were collected from surgical participants who newly used and observed 8K UHD endoscopy in patients undergoing surgery from February 2020 to February 2021. Survey items included sense of presence, reality, depth perception, visibility of tissue, eyestrain, and degree of satisfaction for operators and observers, and weight, operability, focus adjustment, physical fatigue, eyestrain, and satisfaction for camera assistants. Participants rated each 8K UHD endoscopic surgery on a one‐to‐five scale (definitively inferior, relatively inferior, equivalent, relatively superior, definitively superior) compared to the existing endoscopy system of each facility. Results: Overall, questionnaire responses from 139 participants assessing 8K UHD endoscopic surgery were collected from surgeries performed in 46 patients. Respective ratings of operators and observers included sense of presence: "superior or relatively superior", 97.8% and 91.5%; reality: "superior or relatively superior", 76.1% and 72.3%; and visibility of tissue: "superior or relatively superior", 93.5% and 87.2%. Weight was rated as "inferior or relatively inferior" by 73.9% of camera assistants and focus adjustment as "inferior" by 60.9% of them. Conclusions: 8K UHD endoscopic surgery enabled identification of surgical anatomies more clearly, provided a sense of presence and reality, and might improve educational effect. Technological development is expected to reduce the burden of camera assistants.